INCIDENCE OF ACUTE LEUKAEMIAS IN ADULT POPULATION ATTENDING TERTIARY CARE CENTRE AS DIAGNOSED BY CYTOCHEMICAL ANALYSIS AND IMMUNOPHENOTYPING - A STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Acute leukaemias are rapidly progressive haematological malignancies characterized by uncontrolled proliferation of immature hematopoietic cells. Early and accurate diagnosis is essential for prompt treatment and improved survival. Cytochemical analysis and immunophenotyping play a crucial role in classifying acute leukaemias into acute lymphoblastic leukaemia (ALL) and acute myeloid leukaemia (AML). Aims: To determine the incidence of acute leukaemias in the adult population attending RIMS and to classify the cases using cytochemical staining and immunophenotyping. Materials and Methods: This study was a hospital-based observational cross-sectional study conducted over a period of 1 year in the Department of pathology, Rajendra Institute of Medical Sciences. Ranchi, Jharkhand, India. The study population comprised adult patients aged ≥18 years who presented with clinical suspicion of acute leukaemia, including symptoms such as anaemia, fever, bleeding tendencies, and abnormal haematological findings. A total of 52 adult patients fulfilling the inclusion criteria were enrolled based on clinical evaluation and laboratory confirmation during the study period. Results: In the present study, a total of 52 patients were evaluated for acute leukaemia. Based on final diagnosis, acute myeloid leukaemia (AML) was found to be the most common type, observed in 34 patients (65.4%), whereas acute lymphoblastic leukaemia (ALL) was diagnosed in 18 patients (34.6%). Conclusion: Acute myeloid leukaemia is more common than acute lymphoblastic leukaemia in adults attending RIMS. Combined use of cytochemical analysis and immunophenotyping significantly improves diagnostic accuracy and is essential for proper classification and management of acute leukaemias.